‘Diaphaneitè’ and Dante: a New Perspective on Pater’s Early Essay - Julia Straub (Cahiers Victoriens et Edouardiens)
Despite acute awareness of Walter Pater’s interest in and use of literary, mythological, philosophical and artistic sources in his own writings, his reception of Dante Alighieri has not been investigated sufficiently yet. This article gives an overview of Pater’s general interest in Dante, seen within the context of the reception of Dante’s works in the Victorian period, but then focuses on Pater’s early essay ‘Diaphaneitè’. Dante, it is argued, attracted Pater’s attention for moral and aesthetic reasons. It is by examining Dante’s presence in Pater’s texts, and particularly in ‘Diaphaneitè’, that we can find central clues to an understanding of Pater’s concepts of beauty and culture. The figure of Beatrice is the embodiment of what Pater admired in Dante. Her figure reflects in interesting ways upon his style, his concept of the ideal diaphanous character, and gender questions.